Analysis of Surface Deformation and Settlement Characteristics Caused by Tunnel Excavation and Unloading. (30th March 2022) - Wang, Xinfeng; Li, Shan; Wei, Youyu; Zhang, Yiying
Abstract : Aiming at the problems of surface deformation and unloading settlement caused by urban tunnel construction, the basic characteristics of surface deformation caused by tunnel construction, the main influencing factors of surface deformation and settlement, and the temporal and spatial evolution law of stress field and displacement field of surface deformation and settlement are studied by using the comprehensive methods of evaluation factor analysis, theoretical research, and numerical simulation. The results show that the surrounding rock deformation of the tunnel is mainly concentrated in the arch crown and arch bottom, and the deformation gradually decreases from the center of the tunnel to the periphery. The surrounding rock of arch crown has sudden settlement, large deformation rate and amount, and poor stability of surrounding rock, and is prone to engineering accidents such as block falling and even collapse. The farther away from the tunnel, the smaller the degree of settlement. As the time step of tunnel excavation increases, the influence area of surface deformation and settlement increases gradually. After the tunnel adopts reasonable lining support, it can effectively prevent soil deformation transmission and restrain tunnel instability deformation, so as to prevent surface deformation and settlement by improving the self stability of surrounding rock and taking lining support and other measures.